Optimalisasi Kegiatan Posyandu dengan Pelatihan Kader melalui Program Kuliah Kerja Nyata Mahasiswa (KKNM) - ari indra susanti; Fedri Ruluwedrata Rinawan (Jurnal Pengabdian dan Pengembangan Masyarakat, 2019)
The KKN program is an effort to develop student creativity in helping and jumping directly to the problems that exist in society. That problem, including the lack optimal functioning of posyandu, such as recording and reporting of data that is still manual, lack of funds, and lack of cadre knowledge in Giving Additional Foods (PMT) varies. The community service activities are part of KKN activities many of 12 people  consisting of the Faculty of Government and Social Sciences, MIPA Faculty, Food Engineering Faculty, and Psychology Faculty. This activity was held in October until November 2018 in Pasawahan village. This activity is in the form of various training for cadres, such as training for the use of the iposyandu application for recording and reporting data during posyandu activities, training on Additional Food Making (PMT) to be given to toddlers who come to Posyandu as well as business fund training and sponsorship. Cadres were given a pretest and posttest before and after the training was given. With the implementation of various trainings, cadre knowledge and skills are improving in managing and implementing posyandu activities.